High-fidelity simulations of the flow around wings at high reynolds numbers - Vinuesa, Ricardo; Negi, Prabal S.; Hanifi, Ardeshir; Henningson, Dan S.; Schlatter, Philipp (10th International Symposium on Turbulence and Shear Flow Phenomena, TSFP 2017, 2017)
Reynolds-number effects in the adverse-pressure-gradient (APG) turbulent boundary layer (TBL) developing on the suction side of a NACA4412 wing section are assessed in the present work. To this end, we conducted a well-resolved large-eddy simulation of the turbulent flow around the NACA4412 airfoil at a Reynolds number based on freestream velocity and chord length of Rec = 1;000;000, with 5° angle of attack. The results of this simulation are used, together with the direct numerical simulation by Hosseini et al. (Int. J. Heat Fluid Flow 61, 2016) of the same wing section at Rec = 400;000, to characterize the effect of Reynolds number on APG TBLs subjected to the same pressure-gradient distribution (defined by the Caluser pressure-gradient parameter β). Our results indicate that the increase in inner-scaled edge velocity U+e, and the decrease in shape factor H, is lower in the APG on the wing than in zero-pressure-gradient (ZPG) TBLs over the same Reynolds-number range. This indicates that the lower-Re boundary layer is more sensitive to the effect of the APG, a conclusion that is supported by the larger values in the outer region of the tangential velocity fluctuation profile in the Rec = 400;000 wing. Future extensions of the present work will be aimed at studying the differences in the outer-region energizing mechanisms due to APGs and increasing Reynolds number.
CRIS-Team Scopus Importer:2023-03-21